2023
DOI: 10.3390/ma16103638
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of (K0.5Na0.5)NbO3 Single Crystals Grown by Seed-Free and Seeded Solid-State Single Crystal Growth

John G. Fisher,
Su-Hyeon Sim,
Trung Thành Ðoàn
et al.

Abstract: (K0.5Na0.5)NbO3-based piezoelectric ceramics are of interest as a lead-free replacement for Pb(Zr,Ti)O3. In recent years, single crystals of (K0.5Na0.5)NbO3 with improved properties have been grown by the seed-free solid-state crystal growth method, in which the base composition is doped with a specific amount of donor dopant, inducing a few grains to grow abnormally large and form single crystals. Our laboratory experienced difficulty obtaining repeatable single crystal growth using this method. To try and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…However, it can be seen that the amounts of alkali cations were reduced during sintering compared to the nominal composition, and the loss was higher for K compared to Na in both the single crystal and matrix. This alkali volatilization was also observed during calcination and sintering of (K 0.5 Na 0.5 )NbO 3 -based ceramics or single crystals [41,49]. The higher K loss is due to its higher partial pressure compared to Na [22].…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…However, it can be seen that the amounts of alkali cations were reduced during sintering compared to the nominal composition, and the loss was higher for K compared to Na in both the single crystal and matrix. This alkali volatilization was also observed during calcination and sintering of (K 0.5 Na 0.5 )NbO 3 -based ceramics or single crystals [41,49]. The higher K loss is due to its higher partial pressure compared to Na [22].…”
Section: Resultsmentioning
confidence: 68%
“…The size of the single crystals may be improved by choice and optimization of different sintering additives, as carried out for KNN [32,72,73]. In recent work in our laboratory, it has been found that use of a Ba(Cu 0.13 Nb 0.66 )O 3 additive and a [001]-oriented KTaO 3 seed crystal allowed growth of a large and dense single crystal of (K 0.5 Na 0.5 )NbO 3 , although problems with repeatability persisted [49]. Figure S6 shows an SEM micrograph of a 98KNN-2BNZS single crystal (with the addition of 0.15 mol% Li 2 CO 3 and 0.15 mol% Bi 2 O 3 sintering aids as before) grown at 1150 • C for 20 h using a [001]-oriented KTaO 3 seed crystal.…”
Section: Resultsmentioning
confidence: 99%